Post-COVID postural orthostatic tachycardia syndrome (POTS): a new phenomenon - Cantrell, Christopher; Reid, Conor; Walker, Claudia S.; Stallkamp Tidd, Samantha J.; Zhang, Ryan; Wilson, Robert (Frontiers in Neurology, 2024)
BACKGROUND: The impact of COVID-19 has been far-reaching, and the field of neurology is no exception. Due to the long-hauler effect, a variety of chronic health consequences have occurred for some post-COVID patients. A subset of these long-hauler patients experienced symptoms of autonomic dysfunction and tested positive for postural orthostatic tachycardia syndrome (POTS) via autonomic testing.METHODS: We conducted a chart review of a convenience sample from patients seen by neurologists at our tertiary care center for suspicion of post-COVID POTS. Patients included in our study had clearly defined POTS based on clinical criteria and positive tilt table test, were 81.25% female, and had an average age of approximately 36. Out of 16 patients, 12 had a confirmed positive COVID test result, with the remaining 4 having strong clinical suspicion for COVID infection. Our analysis examined the most bothersome 3 symptoms affecting each patient per the neurologist's note at their initial visit for post-COVID POTS, clinical presentation, comorbidities, neurological exam findings, autonomic testing results, and COMPASS-31 autonomic questionnaire and PROMIS fatigue survey results. RESULTS: Palpitations (68.75%) and fatigue (62.5%) were the most common of the impactful symptoms reported by patients in their initial Cleveland Clinic neurology visit. The most frequent comorbidities in our sample were chronic migraines (37.5%), irritable bowel syndrome (IBS) (18.75%), and Raynaud's (18.75%). Neurological exam findings and autonomic testing results other than tilt table yielded variable findings without clear trends. Survey results showed substantial autonomic symptom burden (COMPASS-31 autonomic questionnaire average score 44.45) and high levels of fatigue (PROMIS fatigue survey average score 64.64) in post-COVID POTS patients. CONCLUSION: Our sample of post-COVID POTS patients are similar to the diagnosed POTS general population including in comorbidities and autonomic testing. Fatigue was identified by patients as a common and debilitating symptom. We hope that our study will be an early step toward further investigation of post-COVID POTS with focus on the trends identified in this chart review.